AMIGO and friends: An emerging family of brain-enriched, neuronal growth modulating, type I transmembrane proteins with leucine-rich repeats (LRR) and cell adhesion molecule motifs - Chen, Y. (2011)
10.1016/j.brainresrev.2005.11.005